2022
DOI: 10.1111/cobi.13883
|View full text |Cite
|
Sign up to set email alerts
|

Growth of non‐English‐language literature on biodiversity conservation

Abstract: English is widely recognized as the language of science, and English‐language publications (ELPs) are rapidly increasing. It is often assumed that the number of non‐ELPs is decreasing. This assumption contributes to the underuse of non‐ELPs in conservation science, practice, and policy, especially at the international level. However, the number of conservation articles published in different languages is poorly documented. Using local and international search systems, we searched for scientific articles on bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 45 publications
0
39
0
Order By: Relevance
“…For example, a recent review of twelve major biodiversity databases suggested that variability in taxonomic and geographic scopes and potential incompatibility of metadata are major barriers to data integration (45). Second, many biases are intrinsic to biodiversity databases (17,38,50), suggesting that some of the data we need still await to be collected from the field (51), existing collections (52), or even "grey" literature (53,54), all requiring gigantic human effort. Ultimately, it seems we are being flooded by repeated data on the same taxa [e.g., in 2020, vertebrates accounted for 68% of GBIF-available data; (17)], increasing biases in inadvertent ways (2).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent review of twelve major biodiversity databases suggested that variability in taxonomic and geographic scopes and potential incompatibility of metadata are major barriers to data integration (45). Second, many biases are intrinsic to biodiversity databases (17,38,50), suggesting that some of the data we need still await to be collected from the field (51), existing collections (52), or even "grey" literature (53,54), all requiring gigantic human effort. Ultimately, it seems we are being flooded by repeated data on the same taxa [e.g., in 2020, vertebrates accounted for 68% of GBIF-available data; (17)], increasing biases in inadvertent ways (2).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the number of non-English-language conservation articles published annually has been increasing over the past 39 years, at a rate similar to English-language articles (Chowdhury et al, 2022).…”
Section: Global Evidence In Multiple Languagesmentioning
confidence: 99%
“…When developing search strategies (Stage 1), identifying appropriate sources of non-Englishlanguage evidence (e.g. bibliographic databases) is key, as few international sources index non-English-language evidence (Chowdhury et al, 2022). For example, non-English-language literature is searchable on Google Scholar (https://scholar.google.com) using non-Englishlanguage keywords.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Information on butter y migration is often published in non-peer-reviewed journals [i.e, grey literature] [11], and up to one third of scienti c documents related to biodiversity conservation are published in languages other than English [27]. Ignoring the non-English-language and grey literature can severely bias our understanding [28][29][30][31][32][33][34]. Here we compile a global knowledge base on butter y migration from multiple sources, including peer-reviewed papers and grey literature [including web articles] that are available in English or ve other languages.…”
Section: Introductionmentioning
confidence: 99%